Community based Asian agrifuture: How it can be achieved - Nobutaka Ito (2020)
© The Authors, published by EDP Sciences, 2020. Asia is one of the most productive agricultural regions in the world, however the quality control of agricultural food products should be severely and strictly managed from the view point of food security and safety due to the increase of food feeding demand to cover the drastic and rapidly increase of world human population in recent years. In this paper the current status of Asian agriculture is overviewed first, then the Asian agrifuture is discussed and proposed from the community based viewpoint how it should / can be promoted and achieved.